“STUDY OF KNOWLEDGE, ATTITUDE AND PRACTICE OF MOTHERS ABOUT IMMUNIZATION OF CHILDREN UNDER 5 YEARS OF AGE AMONG MIGRANT WORKERS IN AND AROUND SURATHKAL, KARNATAKA” - Dr. Deepak K.; Dr. Kiran Raj H.; Dr. Harshith R Shetty; Dr. Edwin Dias; Dr. Pooja Naik; Dr. Shruthi M. (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Vaccination is one of the most effective preventive measures for reducing child morbidity and mortality. Over the years, vaccines have proven to be a highly cost-effective public health intervention, minimizing avoidable human suffering, reducing healthcare expenditures, and mitigating economic consequences such as lower productivity and lost workdays. According to the WHO, vaccine-preventable diseases still cause 1.5 million child deaths annually, primarily due to inadequate vaccination coverage.